Elucidating the role of APOE ε4 gene variants in the clinical manifestation of Parkinson's disease - Soraya, Gita Vita; Fitrah, Yusran Ady; Bintang, Andi Kurnia; Akbar, Muhammad; Jannah, Alfi Raudatil; Ulhaq, Zulvikar Syambani; Tammasse, Jumraini; Kaelan, Cahyono; Massi, Muhammad Nasrum; Obinata, Ai; Hara, Norikazu; Miyashita, Akinori; et al. (Frontiers in Aging Neuroscience, 2025)
IntroductionParkinson's Disease (PD) is the most common movement disorder, and remains a major cause of mortality and morbidity worldwide. Studies have uncovered the potential role of the Apolipoprotein (APOE) gene in PD, although results have been conflicting. This study aimed to characterize the APOE ε4 status of Indonesian PD subjects and perform a meta-analysis to elucidate it's role in PD onset age, disease severity, and cognition.MethodsAPOE ε4 genotyping was performed on PD patients and their respective healthy families. Clinical parameters were obtained from PD patients. Secondly, we conducted a meta-analysis on the role of APOE ε4, with studies collected until January 2025. Retrieved parameters include the number of PD APOE ε4 allele carriers and non-carriers, age of onset, disease severity, and mini-mental state examination (MMSE) scores.ResultsFour of the 7 recruited subjects were APOE ε4 carriers, with 2 out of 3 PD subjects of APOE ε4 carrier status. In the meta-analysis, 14 included studies revealed a significantly younger age of onset in APOE ε4 carriers (SMD = −0.16, 95%CI −0.24 to −0.08, p = 0.0001) relative to non-carriers. Six included studies revealed no significant difference in the Hoehn and Yahr disease severity, and 4 included studies showed no significant difference in MMSE scores of carriers vs. non-carriers.ConclusionThe APOE ε4 allele is common in this preliminary study of 3 PD subjects. Our meta-analysis revealed a significantly earlier age-of-onset among APOE ε4 carriers relative to non-carriers, but no difference in disease severity and MMSE scores.